2021
DOI: 10.1177/03795721211061924
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Animal Foods for Nutrition Security and Child Health

Abstract: Background: Aquatic animal source foods (AASF) can provide vital nutrients and bioactive factors essential for human health, yet disparities in consumption patterns prevail globally. Limited evidence exists for the implications of AASF access on child health outcomes. Objective: This study aimed to examine global AASF intakes longitudinally in association with critical nutrient intakes and childhood stunting and anemia. Methods: The analysis draws from compiled longitudinal country data (1993-2013) based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…For example, fish intake was reportedly higher in Malawian children than in Ecuadorian children. However, further inquiry revealed that Malawian infants were given broth made using fish, but very little meat, and were therefore not gaining beneficial calories and nutrients, including iron, calcium, and zinc, provided by fish intake 58 . Children in the Mazira project had overall lower total intakes of protein, vitamin C, iron and zinc from complementary foods compared to the children living in Ecuador 57 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, fish intake was reportedly higher in Malawian children than in Ecuadorian children. However, further inquiry revealed that Malawian infants were given broth made using fish, but very little meat, and were therefore not gaining beneficial calories and nutrients, including iron, calcium, and zinc, provided by fish intake 58 . Children in the Mazira project had overall lower total intakes of protein, vitamin C, iron and zinc from complementary foods compared to the children living in Ecuador 57 .…”
Section: Discussionmentioning
confidence: 99%
“…These foods provide critically important macronutrients such as docosahexaenoic acid and the micronutrients iron, zinc and iodine, which are vital for brain development. Recent evidence highlights the potential for aquatic foods in assuaging child malnutrition problems globally [ 67 , 68 ]. Insects also commonly appeared in our review of the literature, perhaps in part due to the ease of foraging by children.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, dietary guidelines recommend fish as part of sustainable healthy diets, up to 28 g/d (Willett et al, 2019). It is known that dietary fish consumption has been linked to human health outcomes associated with the prevention of stroke and cardiovascular disease, as well as fish consumption during pregnancy is linked to the neurodevelopment of offspring (Iannotti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%